Safety Driving Factors on Palm Oil Transporting Trucks - Sulasmi Sari; Endang Maryanti; Haslinah Haslinah (Hasanuddin Medan, 2022)
As many as 67% of accident victims in 2011 were between the ages of 22 and 50, according to WHO data. There were around 400 thousand victims under the age of 25, with a death toll of 1000 children and teenagers every day on average throughout this time period. PT. Tapian Nadenggan Langga Payung was the focus of this study, which sought to identify the elements that contributed to the safety of oil palm transport trucks. Analytical research with a cross-sectional approach was the research design employed. There are 35 people in total, all of whom work as oil palm fruit truck drivers. In this case, total sampling was employed as the method of sampling. For the knowledge collected from the chi-square test findings, the p value (0.270) was found to be greater than the 0.05 threshold for p value (0.000) based on age and safe driving. Physical Fatigue, on the other hand, has a p value (0.000) 0.05 in the chi-square test. No one's age has any bearing on how safe they are on the road when driving. Driving oil palm transport trucks for PT. Tapian Nadenggan Langga Payung was made more dangerous by lack of experience and exhaustion. Companies should ask their employees, especially truck drivers, to participate in safety driving instruction before they get behind the wheel of a truck.